Pathomorphology of Ameloblastomas - O. Tymofieiev; N. Ushko (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2022)
Objective. To study the pathomorphological structure of ameloblastomas and work out their classification. Materials and methods. Histological analysis of the material obtained after the removal of ameloblastomas of the jaws in 67 patients was carried out. Results. Pathomorphological classification of ameloblastomas of the jaws was suggested based on the studies carried out. Conclusions. The term "ameloblastoma" refers to two groups of tumours: true ameloblastomas and pseudoameloblastomas. Eight structural types of true ameloblastoma may occur, including follicular, plexiform, acanthomatous, basal-cell, granular-cell, desmoplastic, cystic, and mixed. Ameloblastic fibroma, adenoameloblastoma, ameloblastic fibrodontoma and odontoameloblastoma belong to pseudoameloblastomas. The study was performed following the principles of the Declaration of Helsinki. The authors declare no conflict of interest.